2015
DOI: 10.1371/journal.pone.0115042
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Putative Apoplastic Effectors from the Nematode, Globodera rostochiensis, and Identification of an Expansin-Like Protein That Can Induce and Suppress Host Defenses

Abstract: The potato cyst nematode, Globodera rostochiensis, is an important pest of potato. Like other pathogens, plant parasitic nematodes are presumed to employ effector proteins, secreted into the apoplast as well as the host cytoplasm, to alter plant cellular functions and successfully infect their hosts. We have generated a library of ORFs encoding putative G. rostochiensis putative apoplastic effectors in vectors for expression in planta. These clones were assessed for morphological and developmental effects on p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
64
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(64 citation statements)
references
References 69 publications
0
64
0
Order By: Relevance
“…However, in contrast with Mg16820, the different activities of Msp40 appeared in the same cell compartment, the nucleus and cytoplasm, whereas Mg16820 works in the apoplast as well as in the cytoplasm. The Globodera rostochiensis effector GrUBCEP12, with and without SP, was able to suppress several elicitor‐induced cell death pathways (Ali et al, ). Although it was not confirmed by subcellular localization that the effector GrUBCEP12 was indeed transported to the apoplast, it was confirmed that this effector works on several HR pathways.…”
Section: Discussionmentioning
confidence: 99%
“…However, in contrast with Mg16820, the different activities of Msp40 appeared in the same cell compartment, the nucleus and cytoplasm, whereas Mg16820 works in the apoplast as well as in the cytoplasm. The Globodera rostochiensis effector GrUBCEP12, with and without SP, was able to suppress several elicitor‐induced cell death pathways (Ali et al, ). Although it was not confirmed by subcellular localization that the effector GrUBCEP12 was indeed transported to the apoplast, it was confirmed that this effector works on several HR pathways.…”
Section: Discussionmentioning
confidence: 99%
“…To generate the 35S:R-LUC-expressing construct, the pGreenII61 MCS (including the 35S expression cassette) was first subcloned into the AscI and StuI sites of pEAQ-SelectK (Sainsbury et al, 2009) to produce the pEAQ-SE expression vector (Ali et al, 2015). Subsequently, Renilla luciferase was excised from pRL-SV40 (Promega) with NheI and XbaI and cloned into the XbaI site of pEAQ-SE.…”
Section: Plasmid Constructionmentioning
confidence: 99%
“…Multiple effectors from plant‐parasitic nematodes have been shown to suppress basal and/or hypersensitive cell death response (HR)‐related immune responses, and their mechanisms include scavenging reactive oxygen species (Chen et al ., ; Lin et al ., ), nonphotochemical quenching (Lozano‐Torres et al ., ) and less well‐understood mechanisms (Chronis et al ., ; Ali et al ., ,b; Chen et al ., ). Some of these effectors can even activate immune responses (Lozano‐Torres et al ., ; Ali et al ., ,b). In heterologous assays, we found that HgGLAND18 ‐ sp strongly suppresses both canonical basal and HR immune responses.…”
Section: Discussionmentioning
confidence: 97%